PEMBENTUKAN KARAKTER KEDISIPLINAN PADA SISWA SEKOLAH DASAR NEGERI MAMBANG KECAMATAN MUARA KELINGI KABUPATEN MUSI RAWAS MELALUI PERMAINAN RAKYAT - Rusmana Dewi; Nur Nisai Muslihah; Tri Astuti; M. Syahrun Effendi (LP4MK STKIP PGRI Lubuklinggau, 2023)
This community service aims to reintroduce folk games to elementary school students. The aim and target of this activity are students of the State Elementary School in Mambang Village, Muara Kelingi District, Musi Rawas Regency so they can get to know and play folk games. The methods used in the activities are lecture, demonstration, simulation and practice methods. The material presented in this activity includes; Definition of Folk Games, Benefits of Folk Games, Types of Folk Games, How to Play in Folk Games, and Practice of Playing Folk Games, Character Values ​​of Discipline in each Folk Games. The results of the Community Service activities showed that as many as 86 students from the Public Elementary School in Mambang Village, Muara Kelingi District, Musi Rawas Regency who participated in this activity were very enthusiastic about playing folk games. The games practiced are the Cengkleng game, the Rubber Rope game, the Congklak Dakon game, the Wooden Stilts game, the Bekel Ball game and the Shell Stilt game.